Nanocellulose and dispersion thereof
By oxidizing cellulose and disfixing the fiber treatment, nanocellulose without N-oxy compounds was prepared, which solved the problems of its dispersion stability and environmental impact, and achieved high light transmittance and good Slurry characteristics.
Patent Information
- Application Number
- CN202411207250.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-09
- Filing Date
- 2021-07-09
- Publication Date
- 2024-12-13
AI Technical Summary
The dispersion stability of nanocellulose in the dispersion medium is insufficient, and there are residues of N-oxy compounds, which affects the environment and human health.
The nanocellulose obtained by defibrillation treatment is made by using hypochlorous acid or its salt to ensure that it does not contain N-oxy compounds, and the fiber width is controlled between 1 nm and 200 nm and the aspect ratio is between 20 and 150. In between, the Zeta potential is less than -30 mV, and a nanocellulose dispersion with high light transmittance is formed.
The excellent dispersion stability of nanocellulose in the dispersion medium is achieved, which reduces the impact on the environment, and improves the viscosity stability and coating properties of the slurry.
Smart Images

Figure BDA0005019371770000241 
Figure BDA0005019371770000261 
Figure BDA0005019371770000281
Abstract
Description
[0001] This application is a divisional application of an application with a filing date of July 9, 2021, application number 2021800467464, and invention name “Nanocellulose and its dispersion”. Technical Field
[0002] The present invention relates to nanocellulose and a dispersion thereof, and more particularly to nanocellulose obtained by defibrillating oxidized cellulose obtained by oxidizing a cellulose-based raw material with an oxidant, and a nanocellulose dispersion containing the nanocellulose. Background Art
[0003] Various techniques have been proposed for producing nanocellulose materials such as cellulose nanofibers (hereinafter also referred to as CNFs) by oxidizing various cellulose raw materials with an oxidizing agent and refining the obtained oxidized cellulose (see, for example, Patent Documents 1 and 2).
[0004] Patent document 1 discloses the following scheme: using hypochlorous acid or its salt as an oxidant, oxidizing a cellulose-based raw material under high concentration conditions of 14 to 43% by mass of effective chlorine in the reaction system to obtain oxidized cellulose, and defibration and nanofiberization of the obtained oxidized cellulose. Patent document 2 discloses the following scheme: using hypochlorous acid or its salt as an oxidant, making the effective chlorine concentration in the reaction system 6 to 14% by mass, oxidizing a cellulose-based raw material while adjusting the pH to 5.0 to 14.0 to obtain oxidized cellulose, and defibration and nanofiberization of the obtained oxidized cellulose. In these technologies, N-oxyl compounds such as 2,2,6,6-tetramethyl-1-piperidinyl-N-oxyl (TEMPO) are not used as catalysts for oxidation treatment, so N-oxyl compounds do not remain in cellulose fibers, thereby reducing the impact on the environment and producing nanocellulose materials.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2018 / 230354
[0008] Patent Document 2: International Publication No. 2020 / 027307 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] In order to make it easy to mix with other materials (such as resins, etc.), nano cellulose material is sometimes used in a state dispersed in dispersion media such as water, organic solvents, etc. In addition, nano cellulose material is also sometimes mixed with inorganic particles such as pigments and dispersion media, and used in a slurry state. In this case, for nano cellulose material, it is required to show good dispersion stability in the dispersion medium.
[0011] The present invention has been made in view of the above circumstances, and a main object of the present invention is to provide nanocellulose which does not contain an N-oxyl compound in cellulose fibers and has excellent dispersion stability in a dispersion medium.
[0012] Solutions for solving problems
[0013] In order to solve the above-mentioned problems, the present invention provides the following solutions.
[0014] [1] A nanocellulose which is an oxide of a cellulose-based raw material using hypochlorous acid or a salt thereof and has an average fiber width of 1 nm to 200 nm.
[0015] The nanocellulose contains substantially no N-oxyl compounds,
[0016] Zeta potential is below -30mV.
[0017] [2] The nanocellulose according to [1], wherein the average fiber width is from 1 nm to 5 nm.
[0018] [3] The nanocellulose according to [1] or [2], wherein the aspect ratio is 20 or more and 150 or less.
[0019] [4] The nanocellulose according to any one of [1] to [3], wherein the light transmittance of the mixed solution formed by mixing with water to form a solid content concentration of 0.1% by mass is 95% or more.
[0020] [5] A nanocellulose, which is an oxide of a cellulose-based raw material using hypochlorous acid or a salt thereof,
[0021] The nanocellulose does not contain N-oxyl compounds,
[0022] The average fiber width is 1 nm or more and 5 nm or less.
[0023] [6] A nanocellulose which is an oxide of a cellulose-based raw material using hypochlorous acid or a salt thereof and has an average fiber width of 1 nm to 200 nm,
[0024] The nanocellulose does not contain N-oxyl compounds,
[0025] The aspect ratio is 20 or more and 150 or less.
[0026] [7] A nanocellulose which is an oxide of a cellulose-based raw material using hypochlorous acid or a salt thereof and has an average fiber width of 1 nm to 200 nm.
[0027] The nanocellulose does not contain N-oxyl compounds,
[0028] The light transmittance of the mixed solution mixed with water to a solid content concentration of 0.1 mass % is 95% or more.
[0029] [8] A nanocellulose dispersion liquid comprising the nanocellulose according to any one of [1] to [7] dispersed in a dispersion medium.
[0030] Effects of the Invention
[0031] According to the present invention, nanocellulose having excellent dispersion stability in a dispersion medium can be obtained. In addition, since it does not contain an N-oxyl compound, the influence on the environment and the like can be reduced. DETAILED DESCRIPTION
[0032] Nanocellulose
[0033] The nanocellulose disclosed in the present invention (hereinafter also referred to as "the present nanocellulose") is a fibrous nanocellulose obtained by defibrillating oxidized cellulose obtained by oxidizing a cellulose-based raw material with hypochlorous acid or its salt. In addition, the above-mentioned oxidized cellulose can also be referred to as an oxide of a cellulose-based raw material using hypochlorous acid or its salt. The present nanocellulose is described in detail below.
[0034] “Nanocellulose” refers to fibrous cellulose obtained by micronizing oxidized fibrous cellulose, and therefore, is also called “fine cellulose fiber”.
[0035] Nanocellulose is obtained by oxidizing a cellulose raw material with hypochlorous acid or its salt, and therefore, does not substantially contain an N-oxyl compound. Here, in this specification, "does not substantially contain an N-oxyl compound" means that the nanocellulose does not contain an N-oxyl compound at all, or the content of the N-oxyl compound is 2.0 mass ppm or less, preferably 1.0 mass ppm or less relative to the total amount of the nanocellulose. In addition, the content of the N-oxyl compound is preferably 2.0 mass ppm or less, and more preferably 1.0 mass ppm or less, based on the amount of increase from the cellulose raw material, which also means "does not substantially contain an N-oxyl compound".
[0036] By not substantially containing N-oxyl compounds, it is possible to suppress the N-oxyl compounds that are worried about the impact on the environment and the human body from remaining in the nanocellulose. The content of N-oxyl compounds can be measured by known means. As a known means, a method using a trace total nitrogen analysis device can be cited. Specifically, the nitrogen component derived from the N-oxyl compound in the nanocellulose can be measured using a trace total nitrogen analysis device (e.g., Mitsubishi Chemical Analytech, device name: TN-2100H, etc.) with a nitrogen meter.
[0037] ·First embodiment
[0038] [Fiber width]
[0039] The average fiber width of the nanocellulose is 1 to 200 nm. When the average fiber width exceeds 200 nm, the proportion of coarse nanocellulose is large. Therefore, when the nanocellulose is dispersed in the dispersion medium to form a nanocellulose dispersion, there is a tendency for the precipitation of nanocellulose to be large and the quality to be reduced. In addition, the quality of the nanocellulose dispersion is uneven. Therefore, when a slurry (hereinafter also referred to as "nanocellulose-containing slurry") further containing solid particles such as pigments is formed, the viscosity of the slurry is unstable and the operability and coating properties are easily reduced. From this point of view, the average particle size of the nanocellulose is preferably 50 nm or less, more preferably 10 nm or less, and particularly preferably 5 nm or less. In addition, if the average fiber width is less than 1 nm, it becomes close to the form of a cellulose single molecule, and the quality of the nanocellulose tends to become uneven. When the slurry is formed, there is a tendency for the viscosity stability, operability, and coating properties to be easily reduced. Therefore, the average fiber width is preferably 1.2 nm or more, and more preferably 1.5 nm or more.
[0040] In particular, when the average fiber width of the nanocellulose is 1 to 5 nm, in addition to the dispersion stability in the dispersion medium, when a slurry containing the nanocellulose is formed, the viscosity stability, handling properties and coating properties of the slurry can be improved, which is suitable.
[0041] [Aspect Ratio]
[0042] In the present nanocellulose, the aspect ratio (average fiber length / average fiber width) expressed as the ratio of the average fiber width to the average fiber length is preferably 20 to 150. If the aspect ratio is 150 or less, the network of fine cellulose becomes easy to be formed uniformly and densely in the dispersion medium, forming a stable structure, and therefore, the dispersion stability can be improved. In addition, when a slurry containing nanocellulose is formed, it becomes easy to form a network of solid particles and fine cellulose uniformly and densely, which can inhibit the aggregation of solid particles and improve the dispersion stability. Furthermore, the aggregation of solid particles and nanocellulose, or the aggregation of nanocelluloses with each other, can be inhibited, and the improvement of the operability of the slurry and the inhibition of uneven processing can be achieved. From this point of view, the aspect ratio is more preferably 145 or less, further preferably 130 or less, further preferably 120 or less, and further preferably 100 or less.
[0043] On the other hand, when the aspect ratio is too low, that is, when the shape of the nanocellulose is a rod-like shape that is thicker than the elongated fiber-like shape, it is difficult to form a network, aggregation is caused due to uneven existence, and the viscosity stability of the slurry tends to be easily reduced. In addition, the viscosity of the slurry becomes higher, so the operability becomes easy to reduce, and the slurry coating property is sometimes poor. Therefore, the aspect ratio is more preferably 30 or more, more preferably 35 or more, and more preferably 40 or more.
[0044] It should be noted that the average fiber width and the average fiber length are values calculated as follows: nanocellulose is mixed with water in a manner such that the concentration of nanocellulose is approximately 1 to 10 ppm, the fully diluted cellulose aqueous dispersion is naturally dried on a mica substrate, the shape of nanocellulose is observed using a scanning probe microscope, and any number of fibers are randomly selected from the obtained image to form a cross-sectional height of the shape image = fiber width, and a perimeter ÷ 2 = fiber length, thereby calculating the value. Image processing software can be used to calculate such an average fiber width and average fiber length. At this time, the conditions for image processing are arbitrary, but the same image sometimes has differences in the values calculated depending on the conditions for image processing. Regarding the range of the difference in values based on the conditions for image processing, for the average fiber length, it is preferably within the range of ±100 nm. Regarding the range of the difference in values based on the conditions, for the average fiber width, it is preferably within the range of ±10 nm. A more detailed measurement method is based on the method described in the embodiments described later.
[0045] The nanocellulose preferably has a structure in which at least two of the hydroxyl groups of the pyranose glucopyranose ring constituting the cellulose are oxidized, more specifically, a structure in which the hydroxyl groups at the 2nd and 3rd positions of the pyranose glucopyranose ring are oxidized and carboxyl groups are introduced. In addition, it is preferred that the hydroxyl group at the 6th position of the pyranose glucopyranose ring in the nanocellulose is not oxidized but remains a hydroxyl group. It should be noted that the position of the carboxyl group in the pyranose glucopyranose ring of the nanocellulose can be determined according to the solid 13 C-NMR spectroscopy.
[0046] The above solid 13 In the C-NMR spectrum, peaks corresponding to the carboxyl groups at the 2nd and 3rd positions of the glucopyranose ring were observed, and it was determined that the compound had an oxidized structure. At this time, the peaks corresponding to the carboxyl groups at the 2nd and 3rd positions were observed as broad peaks in the range of 165ppm to 185ppm. The broad peaks here can be determined based on the peak area ratio.
[0047] That is, a baseline is drawn on the peak in the range of 165ppm to 185ppm in the NMR spectrum, and after the overall area value is calculated, the ratio of the two peak area values obtained by vertically dividing the area value at the peak top is calculated (large area value / small area value). If the ratio of the peak area values is greater than 1.2, it can be said to be a broad peak.
[0048] In addition, the presence or absence of the above-mentioned broad peak can be judged based on the ratio of the length L of the baseline in the range of 165ppm to 185ppm to the length L' of the vertical line from the peak top to the baseline. That is, if the ratio L' / L is greater than 0.1, it can be judged that a broad peak exists. The above-mentioned ratio L' / L can be greater than 0.2, can be greater than 0.3, can be greater than 0.4, can be greater than 0.5. The upper limit of the ratio L' / L is not particularly limited, and it is usually sufficient as long as it is less than 3.0, can be less than 2.0, or can be less than 1.0.
[0049] In addition, the structure of the glucopyranose ring of the present nanocellulose can also be determined by analysis according to the method described in Sustainable Chem. Eng. 2020, 8, 48, 17800-17806.
[0050] [Zeta potential]
[0051] In one suitable embodiment of the present disclosure, the Zeta potential of the nanocellulose is below -30mV. If the Zeta potential is below -30mV (i.e., the absolute value is above 30mV), the repulsion of microfibers from each other can be fully obtained, and nanocellulose with a high surface charge density becomes easy to produce during mechanical fiberization. Thus, the dispersion stability of the nanocellulose is improved, and the viscosity stability, operability and coating properties when forming the slurry can be excellent. From the viewpoint of dispersion stability, the lower limit of the Zeta potential is not particularly limited. However, when the Zeta potential is above -100mV (i.e., the absolute value is below 100mV), there is a tendency that the oxidative cutting of the fiber direction accompanied by oxidation is suppressed, and therefore, nanocellulose of uniform size can be obtained, which can exert excellent coating properties.
[0052] From the above viewpoints, the Zeta potential of this nanocellulose is preferably below -35mV, more preferably below -40mV, and further preferably below -50mV. In addition, with regard to the lower limit of the Zeta potential, preferably above -90mV, more preferably above -85mV, further preferably above -80mV, further preferably above -77mV, further more preferably above -70mV, and further preferably above -65mV. The range of the Zeta potential can be appropriately combined with the lower limit and upper limit. The Zeta potential is preferably above -90mV and below -30mV, more preferably above -85mV and below -30mV, further preferably above -80mV and below -30mV, further more preferably above -77mV and below -30mV, further preferably above -70mV and below -30mV, and further preferably above -65mV and below -35mV. In this specification, the zeta potential is a value measured under the conditions of pH 8.0 and 20° C. for a cellulose aqueous dispersion obtained by mixing nanocellulose and water to a nanocellulose concentration of 0.1% by mass. Specifically, the zeta potential can be measured under the conditions described in the examples described below.
[0053] [Light transmittance]
[0054] The cellulose fibers of the nanocellulose dispersion in which the nanocellulose is dispersed in the dispersion medium have less light scattering and the like, and can show a high light transmittance. Specifically, in a suitable embodiment, the light transmittance of the mixed solution formed by mixing the nanocellulose with water to form a solid content concentration of 0.1% by mass is 95% or more. Therefore, the nanocellulose and the nanocellulose dispersion containing the nanocellulose can also be widely used for applications requiring transparency, and are useful. The light transmittance is more preferably 96% or more, further preferably 97% or more, and further preferably 99% or more. It should be noted that the light transmittance is a value at a wavelength of 660nm measured using a spectrophotometer.
[0055] [Method for producing nanocellulose]
[0056] Next, the method for producing the nanocellulose of the present invention will be described. The nanocellulose of the present invention can be produced by a method comprising the following steps: step A of oxidizing a cellulose-based raw material with hypochlorous acid or a salt thereof to obtain oxidized cellulose; and step B of defibrillating the oxidized cellulose.
[0057] It should be noted that “oxidized cellulose” is oxidized fibrous cellulose, and therefore, is also referred to as “oxidized cellulose fiber”.
[0058] (Step A: Production of Oxidized Cellulose)
[0059] The cellulose raw material is not particularly limited as long as it is a material containing cellulose as the main component, and examples thereof include pulp, natural cellulose, regenerated cellulose, and fine cellulose obtained by mechanically treating cellulose to depolymerize. As the cellulose raw material, commercially available products such as crystalline cellulose using pulp as a raw material can be used directly. In addition, unused biomass containing a large amount of cellulose components such as tofu dregs and soybean hulls can also be used as raw materials. In addition, in order to facilitate the penetration of the oxidant used into the raw pulp, the cellulose raw material can be treated with an alkali of an appropriate concentration in advance.
[0060] Examples of hypochlorous acid or its salt used for oxidation of the cellulose-based raw material include hypochlorous acid water, sodium hypochlorite, potassium hypochlorite, calcium hypochlorite, and ammonium hypochlorite, etc. Among them, sodium hypochlorite is preferred from the viewpoint of ease of handling.
[0061] As a method for producing oxidized cellulose by oxidation of a cellulose-based raw material, the following method can be cited: a cellulose-based raw material is mixed with a reaction solution containing hypochlorous acid or a salt thereof. In terms of ease of operation and the fact that side reactions are not easily generated, the solvent contained in the reaction solution is preferably water. The effective chlorine concentration of hypochlorous acid or a salt thereof in the reaction solution is preferably 6 to 43% by mass, more preferably 7 to 43% by mass, further preferably 10 to 43% by mass, and further preferably 14 to 43% by mass. If the effective chlorine concentration of the reaction solution is within the above range, the amount of carboxyl groups in the oxidized cellulose can be sufficiently increased, and the oxidized cellulose can be easily defibrated when nanocellulose is obtained.
[0062] From the viewpoint of effectively and sufficiently increasing the amount of carboxyl groups in the oxidized cellulose, the effective chlorine concentration of the reaction solution is more preferably 15% by mass or more, further preferably 18% by mass or more, and further preferably 20% by mass or more. In addition, from the viewpoint of suppressing excessive decomposition of cellulose during fibrillation, the effective chlorine concentration of the reaction solution is more preferably 40% by mass or less, and further preferably 38% by mass or less. The range of the effective chlorine concentration of the reaction solution can be a combination of the above lower limit and upper limit as appropriate. The range of the effective chlorine concentration is more preferably 16 to 43% by mass, and further preferably 18 to 40% by mass.
[0063] It should be noted that the effective chlorine concentration of hypochlorous acid or its salt is defined as follows. Hypochlorous acid is a weak acid that exists in the form of an aqueous solution, and hypochlorite is a compound in which the hydrogen of hypochlorous acid is replaced by other cations. For example, sodium hypochlorite, which is a hypochlorite, exists in a solvent (preferably an aqueous solution), and therefore, the concentration is measured as the effective chlorine amount in the solution rather than the concentration of sodium hypochlorite. Here, with respect to the effective chlorine of sodium hypochlorite, the oxidizing power of the divalent oxygen atom generated by the decomposition of sodium hypochlorite is equivalent to the 2 atomic equivalents of monovalent chlorine, and therefore, the bound chlorine atoms of sodium hypochlorite (NaClO) have the same oxidizing power as the 2 atoms of unbound chlorine (Cl2), resulting in effective chlorine = 2×(chlorine in NaClO). As a specific step of the measurement, first, the sample is accurately weighed, water, potassium iodide and acetic acid are added and allowed to stand, and for free iodine, a starch aqueous solution is used as an indicator and the effective chlorine concentration is determined by titration with a sodium thiosulfate solution.
[0064] The oxidation reaction of the cellulose-based raw material based on hypochlorous acid or its salt can be carried out while adjusting the pH to the range of 5.0 to 14.0. If it is within this range, the oxidation reaction of the cellulose-based raw material can be fully carried out, and the amount of carboxyl groups in the oxidized cellulose can be sufficiently increased. Thereby, the defibration of the oxidized cellulose can be easily carried out. The pH of the reaction system is more preferably 6.0 or more, more preferably 7.0 or more, and more preferably 8.0 or more. Regarding the upper limit of the pH of the reaction system, it is more preferably 13.5 or less, and more preferably 13.0 or less. In addition, the pH range of the reaction system is more preferably 7.0 to 14.0, and more preferably 8.0 to 13.5.
[0065] Hereinafter, the method for producing oxidized cellulose will be further described using the case where sodium hypochlorite is used as hypochlorous acid or a salt thereof as an example.
[0066] When sodium hypochlorite is used to oxidize the cellulose raw material, the reaction solution is preferably an aqueous sodium hypochlorite solution. As a method for adjusting the effective chlorine concentration of the sodium hypochlorite solution to a target concentration (e.g., a target concentration of 6% to 43% by mass), there can be cited a method of concentrating an aqueous sodium hypochlorite solution having an effective chlorine concentration lower than the target concentration, a method of diluting an aqueous sodium hypochlorite solution having an effective chlorine concentration higher than the target concentration, and a method of dissolving sodium hypochlorite crystals (e.g., sodium hypochlorite pentahydrate) in a solvent. Among them, when the effective chlorine concentration as an oxidant is adjusted by a method of diluting an aqueous sodium hypochlorite solution or a method of dissolving sodium hypochlorite crystals in a solvent, there is less self-decomposition (i.e., less reduction in the effective chlorine concentration), and the adjustment of the effective chlorine concentration is simple, so it is preferred.
[0067] The method for mixing the cellulose-based raw material and the sodium hypochlorite aqueous solution is not particularly limited, but from the viewpoint of ease of handling, it is preferred to add the cellulose-based raw material to the sodium hypochlorite aqueous solution and mix them.
[0068] In order to make the oxidation reaction of the cellulose raw material proceed efficiently, it is preferred to carry out the oxidation reaction while stirring the mixed solution of the cellulose raw material and the sodium hypochlorite aqueous solution. As a stirring method, for example, a magnetic stirrer, a stirring rod, a stirrer with a stirring blade (three-in-one motor), a homogenizer, a dispersant mixer, a homogenizer, an external circulation stirring, etc. can be cited. Among them, in terms of the smooth progress of the oxidation reaction of the cellulose raw material and the easy adjustment of the polymerization degree of the oxidized cellulose to a specified value or less, it is preferred to use a shearing stirrer such as a homogenizer and a homogenizer, a stirrer with a stirring blade, and a dispersant mixer. One or more methods are preferably used, and a method using a stirrer with a stirring blade is particularly preferred. When using a stirrer with a stirring blade, as a stirrer, a device equipped with a known stirring blade such as a propeller blade, a paddle blade, a turbine blade, etc. can be used. In addition, when using a stirrer with a stirring blade, it is preferably stirred at a rotation speed of 50 to 300 rpm.
[0069] The reaction temperature in the oxidation reaction is preferably 15°C to 100°C, more preferably 20°C to 90°C. During the reaction, as carboxyl groups are generated in the cellulose raw material by the oxidation reaction, the pH of the reaction system decreases. Therefore, from the viewpoint of making the oxidation reaction efficient, it is preferred to add an alkali agent (such as sodium hydroxide, etc.) or an acid (such as hydrochloric acid, etc.) to the reaction system to adjust the pH of the reaction system to the above-mentioned preferred range. The reaction time of the oxidation reaction can be set according to the degree of oxidation, but is preferably set to about 15 minutes to 50 hours. When the pH of the reaction system is set to 10 or more, it is preferred to set the reaction temperature to 30°C or more and / or the reaction time to 30 minutes or more.
[0070] It should be noted that, by adjusting the reaction times, reaction temperature, stirring conditions etc. of oxidation reaction, thus the fiber width and Zeta potential of nano cellulose can be adjusted to desired values. Specifically, according to extending the reaction time and / or raising the reaction temperature, the oxidation to the cellulose microfiber surface in the cellulose-based raw material is carried out, and electrostatic repulsion, osmotic pressure are utilized, and the repulsion between fibrils is strengthened, thus there is the tendency that average fiber width becomes smaller. In addition, there is more than one (such as extending the reaction time) in the reaction times, reaction temperature and stirring conditions of oxidation set on the side (that is, the side that improves the degree of oxidation) that is further oxidized, thus the tendency of Zeta potential can be improved.
[0071] The carboxyl group content of the oxidized cellulose obtained by the oxidation reaction is preferably 0.30 to 2.0 mmol / g. If the carboxyl group content of the oxidized cellulose is 0.30 mmol / g or more, the fibrillation property of the oxidized cellulose can be sufficiently improved, and nanocellulose with uniform fiber width can be obtained. As a result, the quality of the slurry containing nanocellulose can be made uniform, and the viscosity stability, operability and coating property of the slurry can be improved. On the other hand, if the carboxyl group content is 2.0 mmol / g or less, the excessive decomposition of cellulose during the fibrillation treatment can be suppressed, and nanocellulose with a low ratio of granular cellulose and uniform quality can be obtained. From this point of view, the carboxyl group content of the oxidized cellulose is more preferably 0.35 mmol / g or more, further preferably 0.40 mmol / g or more, further preferably 0.42 mmol / g or more, further more preferably 0.50 mmol / g or more, further preferably more than 0.50 mmol / g, and further preferably 0.55 mmol / g or more. The upper limit of the amount of carboxyl groups may be 1.5 mmol / g or less, 1.2 mmol / g or less, 1.0 mmol / g or less, or 0.9 mmol / g or less. The preferred range of the amount of carboxyl groups can be determined by appropriately combining the upper and lower limits. The amount of carboxyl groups in the present oxidized cellulose is more preferably 0.35 to 2.0 mmol / g, further preferably 0.35 to 1.5 mmol / g, further preferably 0.40 to 1.5 mmol / g, further more preferably 0.50 to 1.2 mmol / g, further preferably more than 0.50 to 1.2 mmol / g, and further preferably 0.55 to 1.0 mmol / g.
[0072] The amount of carboxyl groups (mmol / g) in the oxidized cellulose can be calculated as follows: After adding a 0.1 M hydrochloric acid aqueous solution to an aqueous solution containing oxidized cellulose to adjust the pH to 2.5, a 0.05 N sodium hydroxide aqueous solution is added dropwise, and the conductivity is measured until the pH reaches 11. The amount of sodium hydroxide (a) consumed in the neutralization stage of the weak acid in which the change in conductivity stabilizes can be calculated using the following formula.
[0073] Carboxyl group amount = a (ml) × 0.05 / oxidized cellulose mass (g)
[0074] The solution containing oxidized cellulose obtained by the above reaction is subjected to a known separation treatment such as filtration, and further purified as needed, thereby obtaining oxidized cellulose as an oxide of a cellulose-based raw material using hypochlorous acid or a salt thereof. In addition, before the separation treatment such as filtration, from the viewpoint of improving the filterability and yield of the separation treatment, an acid is added to the solution containing oxidized cellulose, for example, to adjust the pH to 4.0 or less, so that at least a part of the carboxyl groups generated by oxidation are converted into salt forms (-COO - X + :X + refers to cations such as sodium and lithium) that can form protons (-COO - H + ).
[0075] It should be noted that in the infrared absorption spectrum, the proton type is at 1720 cm -1 Peaks and salt types are visible nearby at 1600cm -1 Peaks are visible nearby, so they can be distinguished.
[0076] In addition, the solution containing the oxidized cellulose obtained by the above reaction may be directly subjected to the fibrillation treatment.
[0077] When the pH of a solution containing oxidized cellulose is adjusted to 4.0 or less for separation treatment, in order to improve the operability in the subsequent defibration treatment, for example, alkali is added to adjust the pH to 6.0 or more, so that at least part of the carboxyl groups can be converted into salt forms (-COO - X + :X + The cations are sodium, lithium, and the like.) Alternatively, the solution containing oxidized cellulose may be substituted with its solvent to form a composition containing oxidized cellulose. In the composition containing oxidized cellulose, for example, the pH may be set to an alkaline condition of 10 or higher to convert at least a portion of the carboxyl groups into a salt form (-COO - X + :X + refers to cations such as sodium and lithium).
[0078] The method for producing oxidized cellulose may further include the step of mixing the obtained oxidized cellulose with a compound having a modifying group to control the physical properties of the oxidized cellulose. The compound having a modifying group is not particularly limited as long as it is a compound having a modifying group that can form an ionic bond or a covalent bond with a carboxyl group or a hydroxyl group of the oxidized cellulose. Examples of the compound having a modifying group that can form an ionic bond include primary amines, secondary amines, tertiary amines, quaternary ammonium compounds, and phosphonium compounds. Examples of the compound having a modifying group that can form a covalent bond include alcohols, isocyanate compounds, and epoxy compounds.
[0079] As described above, oxidized cellulose includes salt forms, proton forms, and forms modified by a modifying group. In addition, nanocellulose obtained by the present oxidized cellulose also includes salt forms, proton forms, and forms modified by a modifying group.
[0080] (Process B: Defibrination)
[0081] The present nanocellulose can be obtained by defibrillating and nanofibrillating the oxidized cellulose obtained above. As a method for defibrillating the oxidized cellulose, there can be cited a method based on weak stirring using a magnetic stirrer or the like, a method based on mechanical defibrillation, and the like. In terms of being able to fully defibrate the oxidized cellulose and being able to shorten the defibrillation time, the defibrillation of the oxidized cellulose is preferably based on mechanical defibrillation. Here, nanocellulose (also referred to as nanocellulose) refers to a general term for cellulose nanofibers, including cellulose nanofibers, cellulose nanocrystals, and the like.
[0082] As a method for mechanical fiberization, for example, a method based on various mixing / stirring devices such as a screw mixer, a paddle mixer, a dispersing mixer, a turbine mixer, a homogenizing mixer under high-speed rotation, a high-pressure homogenizer, an ultrahigh-pressure homogenizer, a double-cylinder homogenizer, an ultrasonic homogenizer, a water flow anti-collision type disperser, a beater, a disk refiner, a cone refiner, a double disk refiner, a grinder, a single screw or multi-screw mixer, a self-rotation revolution mixer, and a vibration type mixer can be cited. These devices can be used alone or in combination of two or more, preferably in a dispersion medium, oxidized cellulose is treated so that oxidized cellulose can be nano-sized to produce nanocellulose.
[0083] For the defibration of oxidized cellulose, in terms of being able to effectively produce nanocellulose with further promoted defibration, a method using an ultra-high pressure homogenizer can be preferably used. In the case of a defibration treatment using an ultra-high pressure homogenizer, the pressure during the defibration treatment is preferably 100 MPa or more, more preferably 120 MPa or more, and further preferably 150 MPa or more. The number of defibration treatments is not particularly limited, but from the viewpoint of fully carrying out the defibration, it is preferably 2 times or more, and more preferably 3 times or more. In addition, the above-mentioned oxidized cellulose can also be fully defibrated by gentle stirring using a self-rotating revolution mixer and a vibration-type mixer. As a vibration-type mixer, for example, a vortex mixer (contact mixer) can be cited. That is, according to the above-mentioned oxidized cellulose, when a defibration treatment is carried out under gentle defibration conditions, homogenized nanocellulose can also be obtained.
[0084] The defibration treatment is preferably carried out in a state where the oxidized cellulose is mixed with a dispersion medium. The dispersion medium is not particularly limited and can be appropriately selected according to the purpose. Specific examples of the dispersion medium include water, alcohols, ethers, ketones, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide. As the solvent, one of these may be used alone, or two or more of them may be used in combination.
[0085] Among the above-mentioned dispersion media, alcohols include methanol, ethanol, isopropanol, isobutanol, sec-butanol, tert-butanol, methyl cellosolve, ethylene glycol, and glycerol. Ethers include ethylene glycol dimethyl ether, 1,4-dioxane, and tetrahydrofuran. Ketones include acetone and methyl ethyl ketone.
[0086] During the fibrillation treatment, an organic solvent is used as a dispersion medium, so that the separation of oxidized cellulose and the nanocellulose obtained by fibrillation becomes easy. In addition, in order to obtain the nanocellulose dispersed in the organic solvent, it becomes easy to mix with the resin dissolved in the organic solvent, the resin raw material monomer, etc. The nanocellulose dispersion in which the nanocellulose obtained by fibrillation is dispersed in the dispersion medium of water and / or organic solvent can be used for mixing with various components such as resin, rubber, solid particles, etc.
[0087] The nanocellulose of the above description and the nanocellulose dispersion liquid comprising it can be used for various purposes. Specifically, for example, it can be used as a reinforcing material mixed with various materials (such as resin, fiber, rubber, etc.), or it can also be used as a thickener or dispersant in various purposes (such as food, cosmetics, medical products, coatings, ink, etc.). In addition, the nanocellulose dispersion liquid can also be film-formed, used as various sheets or films. The field of application of this nanocellulose and the nanocellulose dispersion liquid comprising it is not particularly limited either, for example, it can be used in the manufacture of products in various fields such as automotive components, mechanical parts, electrical products, electronic equipment, cosmetics, medical products, building materials, daily necessities, stationery, etc. In addition, for example, using nanocellulose and the nanocellulose dispersion liquid comprising it as the additive to the slurry comprising inorganic particles such as pigment, it is suitable in terms of the viscosity stability, operability, and coating performance of the slurry that can be improved.
[0088] · Second Embodiment
[0089] In a suitable embodiment of the present disclosure, the nanocellulose is a nanocellulose obtained by oxidizing a cellulose raw material with hypochlorous acid or its salt (also referred to as nanocellulose as an oxide of a cellulose raw material using hypochlorous acid or its salt), which does not contain N-oxyl compounds and has an average fiber width of 1 nm or more and 5 nm or less. When the average fiber width of the nanocellulose is 1 to 5 nm, the Zeta potential of the nanocellulose is preferably -25 mV or less, more preferably -30 mV or less, in order to improve the dispersion stability of the nanocellulose and improve the operability when forming the slurry. It should be noted that the description of the first embodiment mentioned above can be used for details of the method for producing the nanocellulose.
[0090] ·Third Embodiment
[0091] In a suitable embodiment of the present disclosure, the nanocellulose is a nanocellulose obtained by oxidizing a cellulose raw material by hypochlorous acid or its salt (also referred to as nanocellulose as an oxide of a cellulose raw material using hypochlorous acid or its salt), which does not contain N-oxyl compounds and has an aspect ratio of 20 to 150. When the aspect ratio of the nanocellulose is 20 to 150, the Zeta potential of the nanocellulose is preferably -25mV or less, more preferably -30mV or less, in order to improve the dispersion stability of the nanocellulose and improve the operability when forming the slurry. It should be noted that the description of the first embodiment above can be cited for details of the method for producing the nanocellulose.
[0092] Example
[0093] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. It should be noted that, hereinafter, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".
[0094] (1) Production of oxidized cellulose and nanocellulose
[0095] [Production Example 1]
[0096] As a cellulose raw material, conifer pulp (NIST RM 8495, bleached kraft pulp, manufactured by SIGMA-ALDRICH) was cut into 5 mm squares with scissors and treated in "WonderBrender WB-1" manufactured by Osaka Chemical.Ind.Co.,Ltd. at 25000 rpm for 1 minute to mechanically defibrate into a cotton-like state.
[0097] In a beaker, 350 g of sodium hypochlorite pentahydrate crystals with an effective chlorine concentration of 42% by mass were placed, and pure water was added and stirred to obtain an aqueous sodium hypochlorite solution with an effective chlorine concentration of 21% by mass. 35% by mass hydrochloric acid was added thereto and stirred to form an aqueous solution with a pH of 11.0. The aqueous sodium hypochlorite solution was heated to 30° C. in a constant temperature water bath while stirring at 200 rpm using a propeller-type stirring blade in a stirrer manufactured by Shinto Science Co., Ltd., and 50 g of the above-mentioned mechanically defibrated coniferous kraft pulp (carboxyl content: 0.05 mmol / g) was added.
[0098] After the cellulose raw material was supplied, the pH during the reaction was adjusted to 11.0 while adding 48% by mass of sodium hydroxide in the same constant temperature water tank while keeping the temperature at 30°C. The mixture was stirred at 200 rpm for 20 minutes using a propeller-type stirring blade in the above-mentioned stirrer to carry out an oxidation reaction. After the reaction was completed, the product was separated into solid and liquid by suction filtration using a PTFE membrane filter with a mesh size of 0.1 μm, and the obtained oxidized cellulose was washed with pure water. The carboxyl group content of the washed filtrate (oxidized cellulose) was measured and found to be 0.37 mmol / g.
[0099] Then, pure water was added to the oxidized cellulose to prepare a 5% dispersion, which was treated with an ultra-high pressure homogenizer "Starburst Lab HJP-25005" manufactured by Sugino Co., Ltd. at 200 MPa and 10 passes to obtain a CNF aqueous dispersion A as a nanocellulose dispersion. It should be noted that in the ultra-high pressure homogenizer, the oxidized cellulose aqueous dispersion was circulated through the ultra-high pressure defibration section built into the ultra-high pressure homogenizer to promote defibration. The amount of liquid passed through the ultra-high pressure defibration section once is referred to as one pass.
[0100] The nitrogen content derived from N-oxyl compounds in the oxidized cellulose was measured as the nitrogen content using a micro total nitrogen analyzer (manufactured by Mitsubishi Chemical Analytech, device name: TN-2100H) and the increase from the raw material pulp was calculated to be 1 ppm or less.
[0101] In addition, the effective chlorine concentration in the sodium hypochlorite aqueous solution was measured according to the following method.
[0102] (Determination of effective chlorine concentration in sodium hypochlorite aqueous solution)
[0103] Accurately measure 0.582g of an aqueous solution of sodium hypochlorite pentahydrate crystals added to pure water, add 50ml of pure water, add 2g of potassium iodide and 10ml of acetic acid, and immediately seal and place in a dark place for 15 minutes. After 15 minutes of placement, free iodine is titrated with 0.1mol / L sodium thiosulfate solution, and the result (indicator starch reagent) and titration amount are 34.55ml. A blank test is separately performed for correction, and 1ml of 0.1mol / L sodium thiosulfate solution is equivalent to 3.545mgCl, so the effective chlorine concentration in the sodium hypochlorite aqueous solution is 21% by mass.
[0104] The carboxyl group content of oxidized cellulose was measured by the following method.
[0105] (Determination of the amount of carboxyl groups)
[0106] To 60 ml of an oxidized cellulose aqueous dispersion having an oxidized cellulose concentration adjusted to 0.5 mass %, a 0.1 M hydrochloric acid aqueous solution was added to adjust the pH to 2.5, and then a 0.05 N sodium hydroxide aqueous solution was added dropwise. The conductivity was measured until the pH reached 11.0. The amount of sodium hydroxide consumed in the neutralization stage of the weak acid at which the change in conductivity stabilized (a) was used to calculate the carboxyl group amount (mmol / g) by the following formula.
[0107] Carboxyl group amount = a (ml) × 0.05 / mass of oxidized cellulose (g)
[0108] [Production Example 2]
[0109] A CNF aqueous dispersion B was obtained by treating under the same conditions as in Production Example 1 except that the reaction time in the oxidation reaction was 30 minutes.
[0110] [Production Example 3]
[0111] A CNF aqueous dispersion C was obtained by treating under the same conditions as in Production Example 1 except that the reaction time in the oxidation reaction was 120 minutes.
[0112] [Production Example 4]
[0113] A CNF aqueous dispersion D was obtained by treating under the same conditions as in Production Example 1 except that the reaction time in the oxidation reaction was 360 minutes.
[0114] [Production Example 5]
[0115] A CNF aqueous dispersion E was obtained by treating under the same conditions as in Production Example 1 except that the reaction time in the oxidation reaction was 480 minutes.
[0116] [Production Example 6]
[0117] A CNF aqueous dispersion F was obtained by treating under the same conditions as in Production Example 1 except that the reaction temperature in the oxidation reaction was changed from 30° C. to 40° C. and the reaction time was changed to 120 minutes.
[0118] [Production Example 7]
[0119] A CNF aqueous dispersion G was obtained by treating under the same conditions as in Production Example 1 except that the reaction temperature in the oxidation reaction was changed from 30° C. to 50° C. and the reaction time was changed to 120 minutes.
[0120] [Production Example 8]
[0121] A CNF aqueous dispersion H was obtained by treating under the same conditions as in Production Example 1 except that the reaction temperature in the oxidation reaction was changed from 30° C. to 40° C. and the reaction time was changed to 480 minutes.
[0122] [Production Example 9]
[0123] A CNF aqueous dispersion I was obtained by treating under the same conditions as in Production Example 1 except that the reaction temperature in the oxidation reaction was changed from 30° C. to 20° C. and the reaction time was changed to 120 minutes.
[0124] [Production Example 10]
[0125] A CNF aqueous dispersion J was obtained by treating under the same conditions as in Production Example 1 except that the reaction time in the oxidation reaction was 15 minutes.
[0126] [Production Example 11]
[0127] A CNF aqueous dispersion K was obtained by treating under the same conditions as in Production Example 1 except that the reaction temperature in the oxidation reaction was changed from 30° C. to 15° C. and the reaction time was changed to 120 minutes.
[0128] The oxidized cellulose obtained in each production example was freeze-dried, and the solid content of the sample was measured after being left at 23° C. and 50% RH for 24 hours or more. 13C-NMR results confirmed that the hydroxyl groups at the 2nd and 3rd positions of the glucopyranose ring were oxidized to introduce carboxyl groups. 13 C-NMR measurement conditions.
[0129] (1) Test tube: Zirconia tube (4mm diameter)
[0130] (2) Magnetic field strength: 9.4T (1H resonance frequency: 400MHz)
[0131] (3) MAS speed: 15kHz
[0132] (4) Pulse sequence: CPMAS method
[0133] (5) Contact time: 3ms
[0134] (6) Waiting time: 5 seconds
[0135] (7) Cumulative times: 10,000 to 15,000 times
[0136] (8) Measurement device: JNM ECA-400 (manufactured by JEOL Ltd.)
[0137] Furthermore, the results of two-dimensional NMR measurements using a model molecule of the oxidized cellulose as a sample also confirmed that the oxidized cellulose obtained in each production example had a structure in which the hydroxyl groups at the 2nd and 3rd positions of the glucopyranose ring were oxidized to introduce carboxyl groups.
[0138] In addition, the solid of the cellulose raw material at position 6 is not found. 13 C-NMR and solid state oxidized cellulose 13 The change in the spectral data of C-NMR showed that the hydroxyl group at position 6 was not oxidized and the oxidized cellulose was directly a hydroxyl group.
[0139] [Comparative Production Example 1]
[0140] As a cellulose raw material, conifer pulp (NIST RM 8495, bleached kraft pulp, manufactured by SIGMA-ALDRICH) was cut into 5 mm squares with scissors and treated in "WonderBrender WB-1" manufactured by Osaka Chemical.Ind.Co.,Ltd. at 25000 rpm for 1 minute to mechanically defibrate into a cotton-like state.
[0141] In a 100 ml beaker, 30.0 g of sodium hypochlorite pentahydrate crystals with an effective chlorine concentration of 43% by mass were placed, and pure water and 35% by mass hydrochloric acid were added and stirred to form an aqueous solution with an effective chlorine concentration of 21% by mass and a pH of 11.0. The sodium hypochlorite aqueous solution was heated to 30° C. in a constant temperature water tank while being stirred with a stirring rod, and 0.35 g of the mechanically defibrated coniferous kraft pulp was added.
[0142] After the cellulose raw material was supplied, 48% by mass of sodium hydroxide was added to maintain the pH at 11.0 in the same constant temperature water tank while being kept at 30°C, and stirred for 30 minutes with a stirring rod. Next, the product was separated into solid and liquid by suction filtration using a PTFE membrane filter with a mesh size of 0.1 μm, and the obtained filtrate was washed with pure water. The carboxyl group content of the washed filtrate (oxidized cellulose) was measured and found to be 0.42 mmol / g.
[0143] The obtained oxidized cellulose was dispersed in pure water to prepare a 5% dispersion, and defibration was performed for 10 minutes in an ultrasonic homogenizer "UP-400S" manufactured by Hilscher under the conditions of CYCLE=0.5 and AMPLIYUDE=50 to obtain a CNF aqueous dispersion P. In the ultrasonic homogenizer, an ultrasonic oscillating part is immersed in the oxidized cellulose aqueous dispersion placed in a container, and defibration is promoted by the ultrasonic wave oscillated from the ultrasonic oscillating part.
[0144] [Comparative Production Example 2]
[0145] As a cellulose raw material, conifer pulp (NIST RM 8495, bleached kraft pulp, manufactured by SIGMA-ALDRICH) was cut into 5 mm squares with scissors and treated in "WonderBrender WB-1" manufactured by Osaka Chemical.Ind.Co.,Ltd. at 25000 rpm for 1 minute to mechanically defibrate into a cotton-like state.
[0146] In a beaker, 30.3 g of sodium hypochlorite pentahydrate crystals with an effective chlorine concentration of 42% by mass were placed, and pure water was added and stirred to make the effective chlorine concentration 14% by mass. 35% by mass hydrochloric acid was added and stirred to form an aqueous solution with a pH of 9.0. The sodium hypochlorite aqueous solution was heated to 30° C. in a constant temperature water bath while being stirred with a stirring rod, and 0.35 g of the mechanically defibrated coniferous kraft pulp was added.
[0147] After the cellulose raw material was supplied, the pH of the reaction was adjusted to 9.0 while adding 48% by mass of sodium hydroxide in the same constant temperature water bath while keeping the temperature at 30°C, and the mixture was stirred for 30 minutes with a stirring rod to perform an oxidation reaction. After the reaction was completed, the product was separated into solid and liquid by suction filtration using a PTFE mesh filter with a mesh size of 0.1 μm, and the obtained filtrate was washed with pure water. The carboxyl group content of the washed filtrate (oxidized cellulose) was measured and found to be 1.12 mmol / g.
[0148] Then, pure water was added to the oxidized cellulose to prepare a 5% dispersion, and defibration treatment was performed in an ultrasonic homogenizer under the same conditions as in Comparative Production Example 1 to obtain a CNF aqueous dispersion Q.
[0149] [Comparative Production Example 3]
[0150] As a cellulose raw material, conifer pulp (SIGMA-ALDRICH NIST RM 8495, bleached kraft pulp) was cut into 5 mm squares with scissors, and treated at 25000 rpm for 1 minute in "WonderBrender WB-1" manufactured by Osaka Chemical.Ind.Co., Ltd., and mechanically defibrated into cotton. The mechanically defibrated cellulose fibers were dispersed in sufficient water, and suction filtered using a PTFE mesh filter with a mesh size of 0.1 μm, thereby obtaining a wet powder.
[0151] The wet powder (80% water by mass, 20 g in terms of dry powder) was placed in a container and then ozone at a concentration of 200 g / m 3 60L of ozone / oxygen mixed gas was added and shaken at 25°C for 2 minutes. After standing for 6 hours, the ozone in the container was removed and the oxidized cellulose was taken out and washed with pure water by suction filtration using a PTFE mesh filter with a mesh size of 0.1μm. Pure water was added to the obtained oxidized cellulose to prepare a 2% by mass dispersion, and sodium hydroxide was added to form a 0.3% by mass sodium hydroxide solution. After stirring for 5 minutes, it was allowed to stand at 25°C for 30 minutes. Then, a PTFE mesh filter with a mesh size of 0.1μm was used to wash it with pure water by suction filtration. The carboxyl group content of the washed oxidized cellulose was measured and the result was 0.43mmol / g.
[0152] Pure water was added to the oxidized cellulose to prepare a 5% dispersion, which was then treated in an ultra-high pressure homogenizer "Starburst Lab HJP-25005" manufactured by Sugino Co., Ltd. at 200 MPa and 10 passes to obtain CNF aqueous dispersion R.
[0153] [Comparative Production Example 4]
[0154] As a cellulose raw material, conifer pulp (NIST RM 8495, bleached kraft pulp, manufactured by SIGMA-ALDRICH) was cut into 5 mm squares with scissors and treated in "WonderBrender WB-1" manufactured by Osaka Chemical.Ind.Co.,Ltd. at 25000 rpm for 1 minute to mechanically defibrate into a cotton-like state.
[0155] 4.92 g of sodium periodate was placed in a beaker, and pure water was added to form an aqueous solution (total amount 600 ml). The sodium periodate aqueous solution was heated to 55° C. in a constant temperature water bath while stirring at 200 rpm using a propeller-type stirring blade in a stirrer manufactured by Shinto Science Co., Ltd., and 6 g of the mechanically defibrated conifer kraft pulp was added.
[0156] After the cellulose raw material was supplied, the mixture was stirred in a stirrer under the same conditions for 3 hours while being kept at 55° C. in the same constant temperature water tank. After the reaction was completed, the product was separated into solid and liquid by suction filtration using a PTFE membrane filter with a mesh size of 0.1 μm, and then washed with pure water.
[0157] Next, the product obtained above was added to a 1M acetic acid aqueous solution containing sodium chlorite, and stirred at 25° C. for 48 hours under the same stirring conditions as above. After the reaction was completed, the product was separated into solid and liquid by suction filtration using a PTFE membrane filter with a mesh size of 0.1 μm, and washed with pure water. The carboxyl group content of the washed oxidized cellulose was measured and found to be 1.72 mmol / g.
[0158] Pure water was added to the obtained oxidized cellulose to prepare a 5% dispersion, and a sodium hydroxide aqueous solution was added to adjust the pH to 7.5, followed by water washing. The obtained dispersion was treated in an ultra-high pressure homogenizer "Starburst Lab HJP-25005" manufactured by Sugino Co., Ltd. at 200 MPa and 10 passes to obtain CNF aqueous dispersion S.
[0159] [Comparative Production Example 5]
[0160] As a cellulose raw material, conifer pulp (NIST RM 8495, bleached kraft pulp, manufactured by SIGMA-ALDRICH) was cut into 5 mm squares with scissors and treated in "WonderBrender WB-1" manufactured by Osaka Chemical.Ind.Co.,Ltd. at 25000 rpm for 1 minute to mechanically defibrate into a cotton-like state.
[0161] 0.016 g of TEMPO and 0.1 g of sodium bromide were placed in a beaker, and pure water was added and stirred to form an aqueous solution, and 1.0 g of the mechanically defibrated conifer kraft pulp was added.
[0162] The aqueous solution was stirred with a stirring rod while heated to 25°C in a constant temperature water bath, and then 0.1M sodium hydroxide was added and stirred to form an aqueous solution with a pH of 10.0. 2.58 g of an aqueous sodium hypochlorite solution with an effective chlorine concentration of 13.2% by mass was added thereto, and the pH of the reaction was adjusted to 10.0 while adding 0.1M sodium hydroxide while keeping the temperature at 25°C in the same constant temperature water bath, and stirred for 120 minutes with a stirring rod.
[0163] After the reaction was completed, the product was separated into solid and liquid by suction filtration using a PTFE membrane filter with a mesh size of 0.1 μm, and the obtained filtrate was washed with pure water. The carboxyl group content of the washed filtrate (oxidized cellulose) was measured and found to be 1.55 mmol / g. Pure water was added to the obtained filtrate to prepare a 5% dispersion, and an aqueous sodium hydroxide solution was added to adjust the pH to 7.5, and washed with water. The obtained dispersion was treated in an ultra-high pressure homogenizer "Starburst Lab HJP-25005" manufactured by Sugino Co., Ltd. at 200 MPa and 10 passes to obtain CNF aqueous dispersion T. The nitrogen component derived from the N-oxyl compound in the oxidized cellulose was measured as the nitrogen content under the same conditions as in Production Example 1, and the increase from the raw pulp was calculated to be 5 ppm.
[0164] [First embodiment]
[0165] [Examples 1-1 to 1-9, Comparative Examples 1-1 to 1-5]: Study on Zeta Potential
[0166] The following evaluations were performed using the CNF aqueous dispersions obtained in each of Production Examples 1 to 9 and Comparative Production Examples 1 to 5 to examine the relationship between the zeta potential and dispersion stability of nanocellulose.
[0167] 〔Zeta potential measurement〕
[0168] Pure water was added to each of the CNF aqueous dispersions A to I, P to T obtained above to dilute the nanocellulose to a concentration of 0.1%. A 0.05 mol / L sodium hydroxide aqueous solution was added to the diluted CNF aqueous dispersion to adjust the pH to 8.0, and the zeta potential was measured at 20°C using a Zeta potentiometer (ELSZ-1000) manufactured by Otsuka Electronics Co., Ltd.
[0169] [Determination of average fiber width]
[0170] Pure water was added to each CNF aqueous dispersion A to I, P to T obtained above, and the concentration of nanocellulose in the CNF aqueous dispersion was adjusted to 5 ppm. The CNF aqueous dispersion after adjusting the concentration was naturally dried on a mica substrate, and the shape of the nanocellulose was observed in AC mode using a scanning probe microscope "MFP-3D infinity" manufactured by Oxford Asylum. For the average fiber width, the software attached to "MFP-3D infinity" was used. For more than 50 fibers, the cross-sectional height of the shape image = fiber width, and the number average fiber width [nm] was calculated.
[0171] 〔Measurement of light transmittance〕
[0172] Each of the CNF water dispersions A to I and P to T obtained above was placed in a quartz cuvette having a thickness of 10 mm, and the light transmittance at a wavelength of 660 nm was measured using a spectrophotometer (JASCO V-550).
[0173] 〔Stability of CNF aqueous dispersion〕
[0174] Pure water was added to each CNF aqueous dispersion A to I, P to T, and diluted so that the concentration of nanocellulose in the CNF aqueous dispersion became 0.1 mass %, and the mixture was left to stand for 4 weeks at 25°C and stored. The solid content concentration in the supernatant was measured immediately after dilution and after 4 weeks of storage, and the dispersion rate was calculated according to the following formula, and the dispersion stability was determined according to the following criteria. The solid content concentration was calculated based on the mass change before and after drying at 105°C.
[0175] Dispersion rate (%) = (solid content concentration after 4 weeks / solid content concentration immediately after dilution) × 100
[0176] ◎: Dispersion rate is less than 95%
[0177] ○: Dispersion rate is 90% or more and less than 95%
[0178] △: Dispersion rate is 85% or more and less than 90%
[0179] ×: Dispersion rate is less than 85%
[0180] 〔Slurry viscosity stability〕
[0181] For aqueous slurries (50 g) containing 5% by mass of titanium oxide (R-820 manufactured by Ishihara Sangyo Co., Ltd.) and each CNF aqueous dispersion A to I, P to T, the amount of nanocellulose added was changed so that the viscosity of the slurry immediately after preparation, i.e., the initial viscosity, was the same in each case (300 mPa·s). For mixing to prepare the aqueous slurry, a mixer "deaerator mixer ARE-310" (mixing mode, revolution: 2000 rpm, rotation: 800 rpm, 20 minutes) of THINKY CORPORATION was used.
[0182] Then, the viscosity immediately after preparation (initial viscosity) and after standing for one week were measured, the viscosity change rate was calculated according to the following formula, and the viscosity stability of the aqueous slurry was determined according to the following criteria.
[0183] Viscosity change rate (%) = (N2 / N1) × 100
[0184] (Wherein, N1 is the initial viscosity of the slurry, and N2 is the viscosity of the slurry after the sample is left to stand for one week.)
[0185] ◎: Viscosity change rate is less than 105%
[0186] ○: Viscosity change rate is 105% or more and less than 110%
[0187] △: Viscosity change rate is 110% or more and less than 115%
[0188] ×: Viscosity change rate is 115% or more
[0189] In addition, the static state was set to indoors (23±2°C).
[0190] The initial viscosity of the slurry and the viscosity after standing for one week were measured in an E-type viscometer (TV-22) manufactured by Toki Sangyo Co., Ltd. at 25°C and 100 rpm (shear rate 200 s -1 ) was measured under the conditions of
[0191] 〔Slurry operability〕
[0192] Water was added to each CNF aqueous dispersion A to I, P to T so that aluminum silicate powder was 5% by mass and nanocellulose was 0.5% by mass, and mixed and stirred to prepare a working liquid. The working liquid was gently stirred with a spatula, and then immediately lifted up, and the sagging when the spatula was tilted was visually observed, and the slurry workability was evaluated according to the following criteria.
[0193] ◎: Sagging occurs immediately upon tilting.
[0194] ○: Sagging occurred after tilting for 5 seconds or more.
[0195] △: Sagging occurred after tilting for 10 seconds or thereafter.
[0196] ×: No sagging occurred even after 15 seconds or thereafter.
[0197] [Surface condition after slurry coating (coating properties)]
[0198] Water was added to each of the CNF aqueous dispersions A to I, P to T so that the aluminum silicate powder was 5% by mass and the nanocellulose was 0.5% by mass, and the mixture was mixed and stirred to prepare a processing liquid. The processing amount of the aluminum silicate powder was 5 g / m 2 The processing liquid was applied to a woven fabric (100% polyester, 100 mm x 100 mm) and dried. Ten woven fabrics after the coating were visually observed for unevenly coated areas (processing unevenness) and evaluated based on the following criteria.
[0199] ◎: No uneven processing was observed in all 10 sheets.
[0200] ○: No uneven processing was observed in sheets 8 to 9.
[0201] △: No uneven processing was observed in sheets 4 to 7.
[0202] ×: No processing unevenness was observed in 1 to 3 sheets, or processing unevenness was observed in all 10 sheets.
[0203] [Table 1]
[0204]
[0205] It should be noted that in Table 1, the case where no N-oxyl compound is used in the oxidation treatment of the cellulose-based raw material (i.e., the case where the CNF dispersion does not substantially contain an N-oxyl compound) is represented by "×", and the case where an N-oxyl compound is used (i.e., the case where the CNF dispersion contains an N-oxyl compound) is represented by "○" (the same applies to the following Tables 2 and 3).
[0206] As shown in Table 1, when comparing Examples 1-1 to 1-9 in which nanocellulose was produced by oxidation treatment using hypochlorite with Comparative Examples 1-1 and 1-2, Examples 1-1 to 1-9 in which the Zeta potential was -30 mV or less showed more excellent slurry properties than Comparative Examples 1-1 and 1-2 in which the Zeta potential was -17.9 mV and -21.7 mV, respectively.
[0207] Specifically, in the CNF aqueous dispersions of Examples 1-1 to 1-9, the dispersion stability of nanocellulose is high. In addition, the slurries obtained in Examples 1-1 to 1-9 have achieved a balance of viscosity stability, operability and coating properties. In particular, in Examples 1-1 to 1-7, the viscosity stability, operability and coating properties of the slurry are all evaluated as "◎" or "○", and the slurry properties are excellent. In addition, from the results of Examples 1-1, 1-2 and 1-9 having the same degree of Zeta potential, it can be seen that compared with Example 1-9 in which the average fiber width of nanocellulose is 5.3nm, Examples 1-1 and 1-2 in which the average fiber width is less than 5nm show better slurry properties.
[0208] In contrast, in Comparative Examples 1-1 to 1-4, the dispersion stability was evaluated as "X", and the slurry properties were also inferior to Examples 1-1 to 1-9. In Comparative Example 1-5, the dispersion stability was good, but the slurry properties were all evaluated as "X".
[0209] [Second embodiment]
[0210] [Examples 2-1 to 2-9, Comparative Examples 2-1 to 2-5]: Study on Average Fiber Width
[0211] The CNF aqueous dispersions A to H, J, P to T obtained in each of Production Examples 1 to 8 and 10 and Comparative Production Examples 1 to 5 were used to perform the same evaluation as in Example 1 to examine the relationship between the average fiber width of nanocellulose and dispersion stability.
[0212] [Table 2]
[0213]
[0214] According to Table 2, when comparing Examples 2-1 to 2-9 in which nanocellulose is produced by oxidation treatment using hypochlorite with Comparative Examples 2-1 and 2-2, Examples 2-1 to 2-9 in which the average fiber diameter is less than 5.0 nm show better slurry properties than Comparative Examples 2-1 and 2-2 in which the average fiber diameters are 5.3 nm and 5.2 nm, respectively.
[0215] In addition, from the results of Examples 2-1 and 2-9 having the same average fiber width, it can be seen that Example 2-1 having a Zeta potential of -30 mV or less showed more excellent slurry properties than Example 2-9 having a Zeta potential of -28.5 mV for nanocellulose.
[0216] [Third embodiment]
[0217] [Examples 3-1 to 3-9, Comparative Examples 3-1 to 3-5]: Study on aspect ratio
[0218] Using the CNF aqueous dispersions A to H, K, P to T obtained in each of the manufacturing examples 1 to 8, 11 and the comparative manufacturing examples 1 to 5, the average fiber length and average fiber width of the nanocellulose were measured, the aspect ratio was calculated, and the same evaluation as in the first embodiment was performed to study the relationship between the aspect ratio and dispersion stability of the nanocellulose. The average fiber length and average fiber width were measured in the following steps.
[0219] [Determination of average fiber length and average fiber width]
[0220] Pure water was added to each CNF aqueous dispersion A~H, K, P~T obtained above, and the concentration of nanocellulose in the CNF aqueous dispersion was adjusted to 5ppm. The CNF aqueous dispersion after adjusting the concentration was naturally dried on a mica substrate, and the shape of nanocellulose was observed in AC mode using a scanning probe microscope "MFP-3D infinity" manufactured by Oxford Asylum. For the average fiber length, the obtained image was binarized and analyzed using the image processing software "Image J". For 100 fibers, the number average fiber length was calculated as fiber length = perimeter ÷ 2. Regarding the average fiber width, the software included with "MFP-3D infinity" was used, and for more than 50 fibers, the number average fiber width [nm] was calculated as the cross-sectional height = fiber width of the shape image. In addition, the aspect ratio was calculated from (average fiber length / average fiber width).
[0221] Table 3 shows the evaluation results.
[0222] [Table 3]
[0223]
[0224] According to Table 3, when comparing Examples 3-1 to 3-9 in which nanocellulose was produced by oxidation treatment using hypochlorite with Comparative Examples 3-1 and 3-2, Examples 3-1 to 3-9 in which the aspect ratio was less than 150 showed more excellent slurry properties than Comparative Examples 3-1 and 3-2 in which the aspect ratio was 183 and 165, respectively.
[0225] In addition, from the results of Examples 3-2 and 3-9 having the same aspect ratio, it can be seen that Example 3-2 having a zeta potential of -30 mV or less showed more excellent slurry properties than Example 3-9 having a zeta potential of -28.6 mV for nanocellulose.
Claims
1. A nanocellulose having a structure in which the hydroxyl groups at the 2nd and 3rd positions of the glucopyranose ring are oxidized to introduce carboxyl groups, and having an average fiber width of 1 nm to 5 nm. Zeta potential is above -77mV and below -30mV, The aspect ratio is 20 or more and 150 or less.
2. The nanocellulose according to claim 1, wherein The light transmittance of the mixed solution mixed with water to a solid content concentration of 0.1 mass % is 95% or more.
3. A nanocellulose having a structure in which the hydroxyl groups at the 2nd and 3rd positions of the glucopyranose ring are oxidized to introduce carboxyl groups, and having an average fiber width of 1 nm to 5 nm. The light transmittance of the mixed solution mixed with water to a solid content concentration of 0.1 mass % is 95% or more. 4 . A nanocellulose dispersion liquid, wherein the nanocellulose according to claim 1 is dispersed in a dispersion medium. 5 . A cosmetic comprising the nanocellulose according to claim 1 or the nanocellulose dispersion according to claim 4 .
